The health guidance process for assistance and family life for patients with psychotic disorder (Research, Society and Development, 2020)
The objective of the study was to discuss the health guidance process related to assistance and family life with patients with psychotic disorder. Exploratory study with a qualitative approach, with the setting of the Psychosocial Care Center (CAPS) in Vassouras, RJ. The study participants were 10 families that accompany users in Mental Health. Using interviews with questions related to the topic. Approved by the Research Ethics Committee of the University of Vassouras, in order to comply with Resolution No. 510/16, on research involving human beings, opinion number 3,433,127. The results showed that a large part of the families of people with psychotic disorders have low socioeconomic power and a low level of education; the majority of the caregivers are female, aged over 40 years and comprised mostly of mothers and / or sisters. There were issues that permeate mental health, referentially under the demand for psychotic disorder. With regard to service management, gaps were found, limiting the articulation of family members with CAPS services, which can reduce the scope of action. Finally, the nurse in the management of the mental health service must use tools for the dissemination of information, focusing on the struggle for social reintegration, greater adherence by family members in meetings and workshops offered to users.